Unique and shared influences of anxiety and ADHD on the behavioral profile of autism in early childhood - Waters, Diana K.; Baranek, Grace T.; Glenn, Elizabeth; Riehl, Hannah; DeMoss, Lauren; Dawson, Geraldine; Carpenter, Kimberly L. H. (Frontiers in Child and Adolescent Psychiatry, 2025)
IntroductionAutism is characterized by a wide range of core and associated behavioral features that can be influenced by co-occurring conditions such as attention-deficit hyperactivity disorder (ADHD) and anxiety disorders. Executive function difficulties are proposed as a common feature of autism and ADHD and are also evident in persons with anxiety disorders. However, little is known about how anxiety disorders or ADHD differentially impact executive functioning or how these difficulties may influence the presentation of core and associated autistic features in young children. In the current study, we explored the unique executive function difficulties associated with co-occurring anxiety and/or ADHD and elucidated how they differentially impact the clinical presentation of autism in young children.MethodsWe assessed 69 autistic children, aged 3 to 5 years. Anxiety and ADHD were assessed through parent interview using the Preschool Age Psychiatric Assessment (PAPA). Executive functions were assessed using the Behavior Rating Inventory of Executive Function – Preschool Version (BRIEF-P). Core autistic features were measured with the Autism Diagnostic Observation Schedule—Second Edition (ADOS-2) and additional features were measured with the Restricted and Repetitive Behaviors Scale, Revised (RBS-R) and the Sensory Experiences Questionnaire (SEQ). Using an additive main effect general linear model, we examined the unique contributions of an anxiety disorder and/or ADHD on core and associated autistic features as well as executive function. Mediation analyses explored the contribution of the executive function profiles to specific features of autism.ResultsResults showed that greater difficulty with attentional shifting was uniquely associated with anxiety, whereas greater difficulty inhibiting behavioral responses was uniquely associated with ADHD. Attentional shifting mediated the relationship between anxiety and ritualistic behaviors, sameness behaviors, sensory hyper-responsivity, and overall autistic features. Conversely, inhibitory control mediated the relationship between ADHD and both irritability and self-injurious behaviors.DiscussionThese findings implicate components of executive functioning as important cognitive processes associated with co-occurring psychiatric conditions in autism. Future research should investigate the impact of early intervention for executive function difficulties on psychiatric and neurodevelopmental outcomes in autistic children.